PENGARUH MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR TEMA LINGKUNGAN BERSIH, SEHAT, DAN ASRI BAGI SISWA KELAS I SEKOLAH DASAR - Heni; Reza Syehma Bahtiar; Noviana Desiningrum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research begins from a background that mathematics is a lesson very difficult for students to learn. The problem in this research shows that the mathematics learning outcomes, which are still low, have not reached the KKM score and students cannot calculate the sum and subtraction very well. The purpose of this research is to determine the effect of student learning outcomes on the theme of clean, healthy, and beautiful environment in class 1 SDN Jemundo 2 Sidoarjo. This research is a quantitative research with Paired Sample T-test analysis, where the independent variable in this research is the use of snakes and ladders, and the dependent variable is the learning outcomes. The population of this research uses all class 1 students of SDN Jemundo 2 Sidoarjo, which consists of 3 classes, but the sample taken was only 1 class, class 1-A, which amounted to 28 students. Sampling was taken by simple random sampling. The research was carried out by using learning outcomes tests. From the results of data analysis, it was obtained Thitung = 29.475 and Ttable = 1.705, so Thitung > Ttable, or 29.475 > 1.705, then Ho was rejected and Ha was accepted, or obtained by sig. (2-tailed) < 0.05 or 0.000 < 0.05, then Ho was rejected and Ha accepted. It can be stated that there is an effect of snake ladder media usage on student learning outcomes on the theme of clean, healthy, and beautiful environment in grade 1 SDN Jemundo 2 Sidoarjo.